Systematic review and meta-analysis of cardiac neurosis for development of clinical practice guidelines of Korean medicine - Park, Hui-Yeong; Lee, Hyun Woo; Song, Geum-Ju; Hong, Sunggyu; Hong, Sunghee; Suh, Hyo-Weon; Yoon, Seok-In; Park, Chan; Chung, Sun-Yong; Kim, Jong Woo (Frontiers in Psychiatry, 2024)
The development of clinical practice guidelines in traditional medicine requires evidence that sufficiently reflects the medical field. Cardiac neurosis is a disease that occurs because of problems in the autonomic nervous system and is characterized by symptoms of the circulatory system that are representative of autonomic dysfunction. In traditional medicine, the heart is considered to be involved in mental health problems, and cardiac neurosis is accompanied by a variety of mental symptoms. Furthermore, there is a categorized diagnosis for cardiac neurosis, and active empirical research is being conducted in China.Objective: This study aimed to systematically review and quantitatively synthesize the effects of Korean medicine treatments in patients with cardiac neurosis to develop evidence-based clinical practice guidelines for the treatment of autonomic dysfunction.Methods: Nine databases were searched for articles published before September 13, 2022. The methodological quality of the studies was assessed using the RoB tool. The primary outcomes were somatization, depression, anxiety, and effectiveness rate. The secondary outcome was the rate of adverse effects.Based on a systematic literature review, 151 randomized controlled trials were selected and analyzed. For patients with cardiac neurosis, herbal medicine, combined treatment of herbal medicine 2 and Western medicine, combined treatment of herbal medicine and acupuncture, acupuncture, and combined treatment of acupuncture and Western medicine showed better overall effects than Western medicine alone. Furthermore, the combined treatment of herbal medicine and psychotherapy and that of herbal medicine, psychotherapy, and Western medicine showed an overall better effect than the combined treatment of Western medicine and psychotherapy.A meta-analysis of articles revealed the effectiveness of Korean medicine treatments and verified the effectiveness of a Korean medicine treatment alone, Korean medicine combined treatment, and combined treatment of Korean medicine and Western medicine on cardiac neurosis. Limitations included the inability to verify the cause of high heterogeneity between studies and the poor quality of the included studies. Nevertheless, this systematic review and meta-analysis of cardiac neurosis showed that the disease concept of traditional medicine can also be organized based on the latest research. Future research related to traditional diseases such as these should be conducted.